Characterizing Early Changes in Quality of Life in Young Women With Breast Cancer - Al-Kaylani, Hend M.; Loeffler, Bradley T.; Mott, Sarah L.; Curry, Melissa; Phadke, Sneha; van der Plas, Ellen (Frontiers in Psychology, 2022)
Introduction Younger age at diagnosis is a risk factor for poor health-related quality of life (HRQOL) in long-term breast cancer survivors. However, few studies have specifically addressed HRQOL in young adults with breast cancer (i.e., diagnosed prior to age 40), nor have early changes in HRQOL been fully characterized. Methods Eligible female patients with breast cancer were identified through our local cancer center. To establish HRQOL, patients completed the Functional Assessment of Cancer Therapy-Breast (FACT-B) around diagnosis and 12 months later. Sociodemographic factors, genetic susceptibility to cancer, tumor- and treatment-related factors, and comorbidities (e.g., depression/anxiety) were abstracted from medical records and the local oncology registry. Mixed-effects models were used to identify changes in FACT-B scores during the first year of treatment and to determine whether any demographic/treatment-related factors modulated changes in scores. Results Health-related quality of life in young patients with breast cancer was within normal limits at baseline, with a FACT-B overall well-being score of 108.5 (95% confidence limits [CI] = 103.7, 113.3). Participants reported slight improvements over a 12-month period: FACT-B overall well-being scores increased 6.6 points (95% CI = 2.1, 11.1, p < 0.01), functional well-being improved 3.0 points (95% CI = 2.0, 4.1, p < 0.01), emotional well-being improved 1.9 points (95% CI = 0.9, 2.8, p < 0.01), and physical well-being improved 1.5 points (95% CI = 0.2, 2.8, p = 0.03), on average. Participants with anxiety/depression at baseline reported greater improvements in FACT-B overall well-being (change: 12.9, 95% CI = 6.4, 9.5) and functional well-being (change: 5.2, 95% CI = 3.5, 6.9) than participants who did not have anxiety/depression at baseline (change in FACT-B overall well-being: 4.9, 95% CI = 0.2, 9.7; change in functional well-being: 2.3, 95% CI = 1.1, 3.4). Marital status, reconstructive surgery, and baseline clinical staging were also significantly associated with changes in aspects of HRQOL, although their impact on change was relatively minimal. Conclusion Young women with breast cancer do not report HRQOL concerns during the first year of treatment. Improvements in HRQOL during the first year of treatment may be attributable to a sense of relief that the cancer is being treated, which, in the short run, may outweigh the negative late effects of treatment.